2012
DOI: 10.1371/journal.pone.0039310
|View full text |Cite
|
Sign up to set email alerts
|

H1N1pdm09 Adjuvanted Vaccination in HIV-Infected Adults: A Randomized Trial of Two Single versus Two Double Doses

Abstract: Background Since human immunodeficiency virus (HIV)-infected individuals are at increased risk of severe disease from pandemic influenza A (H1N1pdm09), vaccination was recommended as a prevention strategy. The aim of the present study was to evaluate the safety, immunogenicity and persistence of the immune response after vaccination against pandemic influenza A (H1N1pdm09) with an adjuvanted vaccine in human immunodeficiency virus (HIV)-infected adults using two single and two double doses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…Participants were approached for study participation from March through August 2011. The sample size was then defined according to criteria presented elsewhere [Santini‐Oliveira et al, ]. All 256 patients included in the 2010 were targeted for immunization and serological assessment in 2011.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants were approached for study participation from March through August 2011. The sample size was then defined according to criteria presented elsewhere [Santini‐Oliveira et al, ]. All 256 patients included in the 2010 were targeted for immunization and serological assessment in 2011.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria for all participants were age 18–59 years and participation in the phase 1 of our investigation [Santini‐Oliveira et al, ], when HIV‐infected individuals received monovalent vaccine against influenza A(H1N1)pdm09. The main exclusion criteria were: receipt of another investigational vaccine or drug in the past 4 weeks, previous anaphylaxis or serious reactions to vaccines, or hypersensitivity to egg and chicken protein or ovalbumin, neurological illness, acute illness on the day of enrolment, pregnancy and breastfeeding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One other study comparing HIV‐positive and HIV‐negative individuals suggested merely quantitative differences in the vaccine responses, thus offering a rationale for boosting strategies in the HIV‐positive population . In HIV‐positive adults however, administering higher/more frequent doses of standard non‐adjuvanted vaccine preparations has not been consistently associated with improved immunogenicity, whilst enhanced responses have been observed with novel adjuvanted preparations . Data on the clinical efficacy of influenza vaccination in HIV‐positive adults are limited.…”
Section: Influenzamentioning
confidence: 99%
“…Inactivated influenza vaccines are safe and well tolerated in HIV‐positive individuals . Injection site reactions are the most frequent side effects.…”
Section: Influenzamentioning
confidence: 99%